Workplace bullying in the nursing profession: A cross-cultural scoping review - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Background: Globally, nurses are at high risk of exposure to workplace bullying, and there is a growing body of literature addressing bullying in the nursing profession. Yet, our understanding of cross-cultural variations in bullying among nurses is lacking. An analysis of what is currently known about bullying in different parts of the world is critical for our understanding of cross-cultural effects of bullying among nurses. Objectives: We aimed to examine workplace bullying research among nurses with the focus on sources, antecedents, outcomes and coping responses from a cross-cultural perspective during the years 20012019. Design: This is a scoping review of published literature on workplace bullying among nurses. Data sources: A literature search was conducted using the CINAHL, PubMed, PsychINFO and Web of Science databases. A total of 166 articles provided data from the following cultural clusters: Anglo, Latin Europe, Eastern Europe, Nordic Europe, Middle East, Latin America, Confucian Asia, Southern Asia and Sub-Saharan Africa. Procedure: Studies were identified through a database search. Relevant data were extracted using a narrative approach. Categories were thematically organized according to the study topics. Cultural differences regarding the variation in the perceptions of and responses to bullying were analysed in relation to the cultural dimensions: power distance, assertiveness, in-group collectivism and performance orientation. Results: Research was mostly conducted in the Anglo cluster. Antecedents and outcomes of bullying were the most often studied topics across all cultural clusters. Vertical bullying was most prevalent in higher power distance cultures, whereas horizontal bullying was either more or equally prevalent in lower power distance cultures. The risk of bullying decreased as nurses' length of service and age increased in most of the clusters. Individual antecedents were more frequently reported in high in-group collectivist cultures. Organizational antecedents such as lack of bullying prevention measures, unsupportive leadership and stressful work characteristics were frequently reported across different cultural clusters. Yet, an organizational culture that tolerates bullying was most commonly addressed in Anglo, a highly performance-oriented culture. Negative outcomes of bullying were very similar across the world. Nurses used emotion-focused coping strategies more frequently almost in all clusters; yet, there were reports of problem-focused coping strategies especially in relatively higher assertiveness cultures. Conclusions: Analysis revealed both similarities and differences in the nurses' reports of bullying by world region. Cultural factors were found to be important for understanding the variation in the nurses' perceptions of and responses to bullying. (c) 2020 Elsevier Ltd. All rights reserved.
Keywords: Cross-cultural; Nursing profession; Scoping review; Workplace bullying; STAFF REGISTERED NURSES; HORIZONTAL VIOLENCE; WORK-ENVIRONMENT; GRADUATE NURSES; PATIENT SAFETY; MEDIATING ROLE; PSYCHOLOGICAL HARASSMENT; EMERGENCY NURSES; JOB-SATISFACTION; MODERATING ROLE